Gestión ambiental comunitaria: desafíos y oportunidades para una comunidad rural de Acapulco, México - Cardona Castaño, Juan Camilo (Pontificia Universidad Católica del Perú, 2025)
Community-based environmental management (CBEM) is an effective tool for addressing environmental issues with the participation of local communities. The objective of this study was to explore the implementation of a CBEM program to address socio-environmental problems, as well as its challenges and opportunities, as perceived from local knowledge—in this case, that of the rural community of El Arenal in Acapulco, Mexico. Field immersion and exploration were used to strengthen CBEM. Additionally, a series of participatory workshops were held with the community to identify socio-environmental issues. Based on the collected information, a SWOT analysis was conducted to identify scenarios of challenges and opportunities. Strategic management (SM) tools were used to perform this analysis. The results showed a preoperational scope, and the strengths, opportunities, weaknesses, and threats indicated that internal conditions are favorable, but external ones are not, as they depend on institutions. In conclusion, the participatory construction of a CBEM program would lead to an improvement in the relationship between the El Arenal community and the Tres Palos lagoon. It would also serve to empower the community in aspects such as control, surveillance, use, utilization, and management of natural resources.

La gestión ambiental comunitaria (GAC) es una herramienta eficaz para abordar los problemas ambientales con la participación de las comunidades locales. El objetivo de este estudio ha sido explorar la implementación de un programa de GAC para abordar los problemas socioambientales, así como sus desafíos y oportunidades, percibidos desde el conocimiento local, en este caso, el de la comunidad rural El Arenal (ciudad de Acapulco, México) y su relación con la laguna de Tres Palos. Se usó la inmersión en campo y la exploración para fortalecer la GAC; además, hubo una serie de talleres participativos con la comunidad para identificar la problemática socioambiental y, a partir de la información recopilada, se realizó un análisis FODA para identificar los escenarios de retos y oportunidades. Se usaron instrumentos de la gestión estratégica (GE) para realizar dicho análisis. Los resultados mostraron que hubo un alcance preoperativo y que las fortalezas, oportunidades, debilidades y amenazas indican que las condiciones internas son favorables, pero las externas no lo son, ya que dependen de las instituciones. Como conclusión, la construcción participativa de un programa de GAC conduciría a un mejoramiento de la relación entre la comunidad de El Arenal y la laguna de Tres Palos. También serviría para empoderar a la comunidad en aspectos como el control, la vigilancia, el uso, el aprovechamiento y la gestión de los recursos naturales.
Community Environmental Management: Challenges and Opportunities for a Rural Community of Acapulco, Mexico
Keywords: Community participation; Community strategies; Local management; Rural community; Socio-environmental problems; Acapulco, Mexico; Comunidad rural; Estrategias comunitarias; Gestión local; Participación comunitaria; Problemas socioambientales; Acapulco, México; https://purl.org/pe-repo/ocde/ford#2.07.01